Finanças públicas e ciclos econômicos : um modelo de equilíbrio geral dinâmico aplicado ao Rio Grande do Sul - Braatz, Jacó (2018)
The state of Rio Grande do Sul has faced structural problems in its finances for decades. Recent cash shortfalls have made clearer imbalances particularly in relation to the deficit structure of public expenditure largely influenced by pension and public debt problems. These situations motivated this thesis to construct a tool for analysis of the state's public finances for the long term, based on the Computable General Equilibrium model, a methodology widely used for the analysis of structural questions about the national and regional economies, its methodological aspect has great capacity to capture the effects of exogenous shocks on several variables of the studied economy. The model developed is the adaptation to the Rio Grande do Sul economy of a dynamic model created for the Australian economy and later North American. The theoretical basis underlying the model created will be the application of the Real Business Cycles, specifically in its shock generator component related to public finances. Such a theory identifies governments as shock-generating agents that produce real effects across the economy and seeks to understand how individuals collectively decide to adjust fiscal policies in response to shocks. As a by-product the adaptation of the modeling to the economy of Rio Grande do Sul, made possible the estimation of a Product Input Matrix of Rio Grande do Sul for the year 2011 with vectors of state revenues and expenses. For simulation exercise in the theoretical and empirical tool developed, shocks in state public spending, involving health, education and social security were simulated. These simulations, besides validating the tool, will outline a long-term picture of the possible effects of shocks in these items, making it possible to evaluate the impacts that these shocks have on the real side of the economy. In the simulations carried out, the model proved to be robust in its medium and long-term projections, since the model was adapted so that it contemplated the relevant aspects of the productive structure of the regional economy, as well as the economic relations of the state with the rest of Brazil and the world. In general, the model produced results consistent with economic theory and other similar studies, showing sufficient dynamics to allow micro-level tracking of the business cycle phenomena that are assumed in the macro predictions and from three scenarios of interest in the public finances of Rio Grande do Sul.